A Renaissance Storybook - Bishop, Morris (Cornell University Press, 2019)
Here for lovers of good stories are twenty-nine Renaissance tales from Italy, France, Spain, Germany, and England. Readers are "urged to read for pleasure, and if they gain instruction by the way, let it be not only in Renaissance life and thought, but in the delightful diversities of human behavior."Some of the narratives, like those of Romeo and Juliet, the Moor of Venice, and Dr. Faustus, are famous; others will probably be new even to those who know the period well. Machiavelli, Cervantes, Margaret of Navarre, Bandello, Deloney, and Breton are among the authors. About half of the selections are newly translated by Mr. Bishop. As in the two previously published volumes, A Classical Storybook and A Medieval Storybook, Alison Mason Kingsbury's illustrations add charm to her husband's book.